Malaysian young adults’ attachment patterns: the relationship with experienced parenting and co-sleeping - Yin, Mun Wan; de Vries, Marieke (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present study investigated the role of experienced parenting styles and previous co sleeping habits in attachment patterns among Malaysian young adults. Eighty-six participants completed the Sleep Arrangement Questionnaire, Parental Authority Questionnaire, and Experiences in Close Relationship-Revised-General Short Form. Hierarchical multiple regression revealed that, while controlling for demographic covariates, an authoritative parenting style significantly related to a lower level of attachment anxiety, whereas an authoritarian parenting style significantly related to a higher level of attachment anxiety. However, the relationship was only found in the dimension of attachment anxiety but not in attachment avoidance, suggesting that attachment avoidance may be more open to influences of later interpersonal experiences other than parent-child relationships. Besides, total co sleeping frequency was not related to attachment patterns. Future research is encouraged to investigate different aspects (location/duration/reason) of co-sleeping that could affect the outcome.